Ecological restoration hierarchy as a lens to reveal the foundational economic and legal structures impeding restoration - Soininen, Niko; Puharinen, Suvi-Tuuli; Iho, Antti; Koljonen, Saija; Artell, Janne; Tolonen, Kimmo; Belinskij, Antti (Wiley-Blackwell, 2026)
Introduction Biodiversity loss is accelerating due to habitat destruction, economic expansion, and insufficient conservation efforts. Traditional mitigation strategies, which focus on minimizing harm rather than reversing damage, are inadequate for achieving net biodiversity gain. Objectives This article introduces the restoration hierarchy, a framework prioritizing full ecosystem restoration over partial restoration and mitigation to implement ambitious restoration efforts along the widely used restoration continuum. Methods The methodology comprises a case study approach combined with a literature review on ecological restoration, economic cost–benefit analysis, and legal analysis into the foundational legal structures impeding restoration. Results Using Finnish dam removals as a case study, we demonstrate that large-scale, full restoration yields not only the greatest ecological benefits, but also the greatest social welfare in a cost–benefit analysis. Despite ecology and economics aligning on restoration, legal structures currently obstruct large-scale restoration by prioritizing short-term private economic interests, protecting existing land-use rights, and limiting ambitious restoration efforts. We identify six key structural biases in law altogether, for instance, property rights, the relative permanence of resource permits, and the limited scope of application of restoration laws. Conclusions The article concludes that both ecological and economic perspectives support the consideration of full restoration at sufficient scale, rather than implementing fragmented restoration measures. Current legal structures in place, however, slow down or impede such ambitious approaches to restoration.
Keywords: biodiversity; cost-benefit analysis; ecology; law; restoration hierarchy